HAEMATOLOGICAL AND BLOOD BIOCHEMICAL PARAMETERS OF PRE - AND POST LAMBING PERIODS FOR IRAQI NUAEMIE EWES - & et al., Awad (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
The present study designed  to investigate the hematological and blood biochemical changes in pre and post lambing periods in Iraqi Nuaemie ewes. Ten Nuaemie ewes weighed 35-45 kg and aged between 2-3 years were reared in animal's house of Veterinary College / Tikrit University from October-2018 to March-2019, Ten ml of blood samples were collected from each animal during the periods of last gestation month, at lambing and 2 weeks thereafter, Two and half ml of blood samples were collected in EDTA- containing tubes to determine the hematological parameters and the remaining was used to separate serum and stored at -20 °c for blood biochemical assessment. The results   revealed decreased in total red blood cells, haemoglobin and packed cell volume during post lambing period. The total white blood cells count and neutrophils were decreased during the post-partum period, while the lymphocyte was decreased at the day of lambing (50±5.8%). The biochemical parameters exhibited lesser total protein concentrations at the day of lambing (6.5± 1.85 g/dl ) while greater glucose, cholesterol and triglyceride concentrations during post-partum period. The concentration of urea and creatinine increased during the pre-partum period whereas, LDL and HDL concentrations increased in post- lambing period. The minerals concentrations revealed lesser concentrations of Zink and iron during the post-partum period while, copper concentration was greater during similar period. In conclusion, the physiological status of animals have clearly effects on the haematological and biochemical parameters in Iraqi Nuaemie ewes.